A comparative review of potential ammonia-based carbon capture systems. (1st June 2021) - Al-Hamed, Khaled H.M.; Dincer, Ibrahim
Abstract: Carbon capturing technologies are recognized as a cornerstone solution in reducing greenhouse gas emissions to meet the 2050 emissions targets set during the past Paris agreement. Recently, ammonia has become a major carbon-free chemical to absorb CO2 emissions from flue gases. In this regard, this paper concerns the recently developed novel ammonia-based carbon capturing systems in the open literature and comparatively evaluates them from various perspectives in addition to discussing their advantages and disadvantages. The systems considered are basically classified into three categories, namely renewable energy-based systems, energy savings-focused systems, and Integrated Gasification Combined Cycle (IGCC)-based systems. Then, comparative assessments of the novel systems are conducted to see their advantages and weaknesses as compared to the typical chilled ammonia process. Generally, the novel systems have significantly lower energy requirements. The highest reduction is 37.3%. Another result of the comparative study is that renewable energy-based systems of carbon capturing have higher operational costs that can reach up to C$136 ton −1 of CO2 captured. Future efforts are expected to focus on reducing these costs since renewable energy-based systems are also used to co-produce chemical commodities, such as urea and ammonium bicarbonate. These high-value commodities have the potential to generate enough economic value to compensate for the operational costs of carbon capturing using ammonia as a chemical solvent. Highlights: Review of recent ammonia-based carbon capture systems. Renewable energy-based carbon capture systems are reviewed and compared. Energy requirements and operational costs are compared. Co-production of useful chemicals will make carbon capture systems self-sustaining.